Optimal Tolerogenic Dendritic Cells in Type 1 Diabetes (T1D) Therapy: What Can We Learn From Non-obese Diabetic (NOD) Mouse Models? - Funda, David P.; Palová-Jelínková, Lenka; Goliáš, Jaroslav; Kroulíková, Zuzana; Fajstová, Alena; Hudcovic, Tomáš; Špíšek, Radek (Frontiers in Immunology, 2019)
Tolerogenic dendritic cells (tolDCs) are explored as a promising standalone or combination therapy in type 1 diabetes (T1D). The therapeutical application of tolDCs, including human trials, is tested also in other autoimmune diseases however, T1D displays some unique features. In addition, unlike in several disease-induced animal models of autoimmune diseases, the prevalent animal model for T1D, the NOD mouse, develops diabetes spontaneously. This review compares evidence of various tolDCs approaches obtained from animal (mainly NOD) models of T1D with focus on parameters of this cell-based therapy such as protocols of tolDC preparation, antigen-specific versus unspecific approach, doses of tolDCs and/or autoantigens, application schemes, application routes, the migration of tolDCs as well as their preventive, early pre-onset intervention or curative effects. This review also discusses perspectives of tolDC therapy and areas of preclinical research that are in need of better clarification in animal models in a quest for effective and optimal tolDCs therapies of T1D in humans.